E-COMMERCE PERLENGKAPAN HAJI DAN UMROH : Berbasis Web Menggunakan Metode Agile Software Developement - Ihsanuddin Rabbani (2020)
In industry 4.0 technology has developed rapidly and the internet has been entrenched in the world community and in Indonesian society. In business activities, technological advances have a positive impact in increasing the efficiency and effectiveness of selling products and marketing these products. Every year Indonesia is a country with the highest number of Hajj and Umrah pilgrims in the world with the number of Hajj pilgrims per year reaching 211 thousand people and Umrah pilgrims can reach 1.1 people. With the various equipment that must be brought when in the Holy Land, prospective pilgrims have difficulty knowing what items are needed and finding places that sell equipment for Hajj or Umrah. Not only from the side of the prospective Jamaah, traders who provide Hajj and Umrah equipment also find it difficult because their selling power is limited. By utilizing E-Commerce, it can make it easier for Hajj and Umrah equipment traders to market their products. Prospective pilgrims who are leaving for the Holy Land will also find it easier to find equipment products that must be purchased when they want to do Hajj or Umrah. E-commerce of this Web-based Hajj and Umrah equipment is built using agile software development to easily adapt to all changing application needs. This Web-based application is built using the Vue.js JavaScript framework, the backend and database use Firebase.